2023
DOI: 10.3390/foods12091897
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Modeling and Genetic Algorithm Multiobjective Optimization of Process of Drying-Assisted Walnut Breaking

Abstract: This study combined an artificial neural network (ANN) with a genetic algorithm (GA) to obtain the model and optimal process parameters of drying-assisted walnut breaking. Walnuts were dried at different IR temperatures (40 °C, 45 °C, 50 °C, and 55 °C) and air velocities (1, 2, 3, and 4 m/s) to different moisture contents (10%, 15%, 20%, and 25%) by using air-impingement technology. Subsequently, the dried walnuts were broken in different loading directions (sutural, longitudinal, and vertical). The drying tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…MATLAB software was used for data processing, model prediction, and real-time display of moisture content in the moisture content online detection system. First, the initial weight and the initial moisture content of the material were set, and the initial moisture content was measured by the oven method ( Yang et al., 2023b ). The sensor cannot detect the tray position and is a fixed value.…”
Section: Principles and Methodsmentioning
confidence: 99%
“…MATLAB software was used for data processing, model prediction, and real-time display of moisture content in the moisture content online detection system. First, the initial weight and the initial moisture content of the material were set, and the initial moisture content was measured by the oven method ( Yang et al., 2023b ). The sensor cannot detect the tray position and is a fixed value.…”
Section: Principles and Methodsmentioning
confidence: 99%
“…The temperature of the inner chamber is regulated by controlling the power of the six infrared heating tubes. An increase in air velocity can significantly increase the drying rate of the material [ 21 ]. As the fan power is a small proportion of the total power of the equipment, an increase in air velocity does not greatly increase the total power of the equipment.…”
Section: Methodsmentioning
confidence: 99%
“…Training a neural network means continuously optimising the weights [ 21 ]. The initial weights are randomly generated, and the training of neural networks is sensitive to the initial weights, which can easily fall into a local optimum if the initial weights are not chosen appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…Fabani et al (Fabani et al 2021) demonstrated that, in convective drying experiments, GA-BP can better represent the drying kinetics of watermelon peels compared to 11 different empirical models. Yang et al (Yang et al 2023) optimized an artificial neural network using GA to effectively Compared with traditional machine learning algorithms, the GA-BP algorithm has unique advantages. The global search capability of the GA can seek optimization of the initial weights and thresholds of the BP neural network, thus improving the prediction accuracy and learning speed of the network.…”
Section: Introductionmentioning
confidence: 99%